Seizures using a nasal decongestant (Sociedade Galega de Medicina Interna, 2015)
Posterior reversible encephalopathy syndrome (PRES) is a well-known clinicoradiological syndrome characterized by severe headache with or without neurological deficits or sei-zures and edema of subcortical white matter in diverse brain areas1,2. The predominant involvement of posterior cerebral lobes may be explained by an augmented vulnerability of this zones in part due to decreased sympathetic innervation and subsequent hyperperfusion and vasogenic edema.